Connecting mathematics and sports in informal learning spaces - Turner, Erin; Buxner, Sanlyn; Miller, Seneca B.; Baze, Christina; Valerdi, Ricardo (Frontiers in Education, 2024)
Introduction There is a critical need to develop innovative educational strategies that engage youth in meaningful mathematics learning, particularly students from groups that have been historically marginalized in science, technology, engineering, and mathematics (STEM). In this study, we explore youths’ participation in two collaborative projects from the Growing Mathletes curriculum which combines baseball contexts and mathematics. Our goal was to understand the potential of these projects to support youths’ engagement with mathematical ideas and practices, and the extent to which youth leveraged a range of resources, including prior experiences and funds of knowledge, to inform their decisions and understanding. Methods The Design a Stadium and Baseball Team Roster projects were implemented in two afterschool setting sites and two summer program sites with 102 youth of all genders in grades 3 to 8. Data sources included video recordings of youth participation in the project, project artifacts, and youth interviews. Results We found the projects contained specific features that supported youths’ engagement in three specific mathematical practices: (1) make sense of problems and persevere in solving them, (2) reason abstractly and quantitatively, and (3) construct viable arguments and critique the reasoning of others. Additionally, there is evidence that while engaging in these projects youth drew on their own funds of knowledge to inform their decisions and understanding. Conclusion Our findings point to key implications for researchers, educators, and curriculum developers in informal STEM learning spaces.